Model Sistem Informasi Pengolahan Data Kepegawaian Dan Arsip Surat Berbasis Web Pada Instansi Disnakertrans - Iik Eliyana Purnama Sari; Depi Rusda (STMIK Banjarbaru, 2022)
The process of processing employee data and administrative services for correspondence with a large volume of data within the Office of Manpower and Transmigration of the East Kotawaringin Regency raises problems related to the effectiveness and efficiency of the process as a result of a work system that is still manual. This study aims to develop a model of data processing information systems and correspondence to be able to improve organizational performance. The User-Centered Design method is used in developing system models so that user adaptation to information systems can occur properly. The User-Centered Design method engages users at various stages during the design and testing process to discuss user requirements. System functions in the form of managing personnel administration and employee family data, with data on incoming and outgoing letters as well as other letters such as Certificates for Obtaining Employee Family Allowance Payments (KP4) and Periodic Letters of the Regional Civil Service Agency (BKD) are tested through the Blackbox Test. The test results show that all functional features work validly.Keywords: Personnel; Correspondence; Functional requirements; User-Centered Design; Black Box TestingAbstrakProses pengolahan data pegawai dan layanan administrasi surat menyurat dengan volume data yang besar di lingkungan Dinas Tenaga Kerja dan Transmigrasi Kabupaten Kotawaringin Timur, menimbulkan masalah terkait efektivitas dan efisiensi proses sebagai akibat dari sistem kerja yang masih manual. Penelitian ini bertujuan mengembangkan model sistem informasi pengolahan data dan surat menyurat untuk dapat meningkatkan kinerja organisasi. Metode User-Centered Design digunakan dalam pengembangan model sistem agar adaptasi pengguna terhadap sistem informasi dapat terjadi dengan baik. Metode User-Centered Design melibatkan pengguna di berbagai tahapan selama proses desain dan pengujian untuk mendiskusikan kebutuhan pengguna. Fungsi-fungsi sistem berupa pengelolaan administrasi kepegawaian dan data keluarga pegawai, dengan data surat-surat masuk dan surat keluar serta surat-surat lain seperti Surat Keterangan Untuk Mendapatkan Pembayaran Tunjangan Keluarga pegawai (KP4) dan Surat Berkala BKD diuji melalui Uji Balckbox. Hasil uji menunjukkan seluruh fitur fungsional telah bekerja secara valid.Kata kunci: Kepegawaian; Surat menyurat; Kebutuhan fungsional; User-Centered Design; Pengujian Black Box